2003
DOI: 10.1074/jbc.m206104200
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A4 Interacts with the Liver Oncoprotein Gankyrin and Suppresses Its Tumorigenic Activity

Abstract: Hepatocellular carcinoma ranks among the most common malignancies in Southeast Asia and South Africa. Although there are many modalities of treatment, the recurrence and metastasis rates are high, and the prognosis is unsatisfactory. Gankyrin, a recently found oncoprotein, is a promising target for drug therapy because it is overexpressed in all studied hepatocellular carcinomas. Gankyrin contains six ankyrin repeats and interacts with Rb, Cdk4, and the S6 ATPase of the 26 S proteasome. In this study, a yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 24 publications
2
70
2
Order By: Relevance
“…12,[31][32][33][34] However, so far there have been no reports on the role of gankyrin in either esophageal cancer or in other gastrointestinal cancers. This study is the first report on gankyrin expression in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…12,[31][32][33][34] However, so far there have been no reports on the role of gankyrin in either esophageal cancer or in other gastrointestinal cancers. This study is the first report on gankyrin expression in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…As for gankyrin, its physiological partners include CDK4 (56,58), Rb (65), S6 ATPase of the 26S proteasome (61), MAGE-A4 antigen (66), and HDM2 (67) (Figure 5c). Binding of gankyrin to Rb, S6 ATPase of the 26S proteasome, and HDM2 facilitates the ubiquitin-mediated degradation of Rb, HDM2, and other proteins (65,(67)(68)(69), while binding of gankyrin to MAGE-A4 quenches the oncogenic activity of gankyrin through unknown mechanisms (66). Protein fragmentation studies have demonstrated that the first four ARs of gankyrin are involved in interacting with CDK4 and the last two ARs are responsible for binding to Rb (59).…”
Section: Specificitymentioning
confidence: 99%
“…10 Subsequently, other groups also described an opposite correlation between MAGE-A gene expression and p53 activity. 7,11,12 Interestingly, only MageA4 has been shown to be involved in some potentially anti-tumor functions such as gankyrin oncoprotein inhibition 13 and apoptosis induction. 14,15 It has been demonstrated that escape to cellular senescence is one of the first barriers to be bypassed during transformation.…”
mentioning
confidence: 99%